Holocaust Distortion and The Journey of Protagonist in Facing Anti-Semitism in ‘The Boy in The Striped Pyjamas’ Film - Haditomo, Arif Patrialis (Cinematology: Journal Anthology of Film and Television Studies, 2023)
The Holocaust was an aggressive act by the Nazis masterminded by Hitler in the extermination of the Jews during World War II in parts of Europe. The act of systemic genocide is a dark world historical event because it took many victims and even left deep trauma for the descendants of the victims of this abomination. In several popular media, the depiction of the Holocaust has been interpreted in different forms, one of which is in the film The Boy in The Striped Pajamas. The film tells of the friendly relationship between Bruno as a Nazi child and Shmuel as a Jewish child who is surrounded by the issue of anti-Semitism in their environment. Bruno as the protagonist seeks social control measures to eliminate these social phenomena so that he can interact more deeply with his friends. This study uses a qualitative method with a descriptive approach. Sources of data come from secondary sources in the form of films and research articles. The results of this study are to find out the factors that gave birth to the Holocaust in the setting of the places used and the attitudes of the characters in carrying out social control to deal with the issue of anti-Semitism in it.